The Role of Fear of Missing Out, Impulsive Buying, and Doom Spending as a Mediator on Ticket Purchase Decisions for International Concerts in Jakarta - Eksakty Pinastika Ivananta Putra; Rahmawati Rahmawati; Saida Zainurossalamia ZA (JURNAL ECONOMINA, 2026)
This study examines the effect of Fear of Missing Out (FoMO) and impulsive buying on purchase decisions, with doom spending as a mediating variable in the context of international concert tickets. Using a quantitative approach and SEM-PLS analysis, data were collected from respondents aged 18–34 who actively use social media. The findings reveal that FoMO and impulsive buying significantly influence purchase decisions, both directly and indirectly through doom spending. This study highlights the important role of psychological and emotional factors in shaping consumer behavior and introduces doom spending as a mediating mechanism in purchase decision processes